2016
DOI: 10.1186/s13075-016-1068-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha, citrullination, and peptidylarginine deiminase 4 in lung and joint inflammation

Abstract: BackgroundThe relationship between lung and joint inflammation in rheumatoid arthritis is poorly understood. Lung inflammation with resultant protein citrullination may trigger anti-citrullinated protein antibodies, inflammation, and arthritis. Alternatively, lung and joint inflammation may be two manifestations of a single underlying pathology. The lung has increased citrullination and TNF-α levels are high in rheumatoid arthritis; however, it is unknown if TNF-α can induce lung protein citrullination. The ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
(15 reference statements)
6
30
1
1
Order By: Relevance
“…This method likely does not detect every citrullinated protein, but use of the citrulline probe rhodamine-phenylglyoxal (Rh-PG) [47] is limited by extensive background and use of the mouse monoclonal anti-peptidylcitrulline antibody F95 [48] is limited by binding of the anti-mouse IgM secondary antibody in murine joint tissue (data not shown). Nonetheless, our finding is consistent with the observation that PAD4 is not required for TNFα-induced lung [31] or serum [25] protein citrullination, as determined by other methods. Thus, we conclude that PAD4 is not required for at least a significant portion of the increased citrullination seen in TNFα-induced arthritis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This method likely does not detect every citrullinated protein, but use of the citrulline probe rhodamine-phenylglyoxal (Rh-PG) [47] is limited by extensive background and use of the mouse monoclonal anti-peptidylcitrulline antibody F95 [48] is limited by binding of the anti-mouse IgM secondary antibody in murine joint tissue (data not shown). Nonetheless, our finding is consistent with the observation that PAD4 is not required for TNFα-induced lung [31] or serum [25] protein citrullination, as determined by other methods. Thus, we conclude that PAD4 is not required for at least a significant portion of the increased citrullination seen in TNFα-induced arthritis.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, we found that TNFα overexpression leads to increased citrullination in inflamed joints consistent with the finding that TNFα drives citrullination in the serum [25] and lung [31]. TNFα may also drive citrullination in the human rheumatoid joint providing fodder for continued inflammation particularly in ACPA + individuals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that (chronic) inflammation induced by smoking and environmental stimuli such as infection can increase the levels of inflammatory cytokines such as TNF-α in the lung and trigger protein citrullination (44,45). The notion that citrullination is an inflammation-dependent process (46) may be substantiated by our observation that the third highest levels of citrullination was found in placenta, a tissue with strong systemic inflammatory responses during normal pregnancy and acute inflammation during labor (47).…”
Section: The Landscape Of Protein Citrullination Of Human Tissuesmentioning
confidence: 99%
“…4a). Using Rh-PG, Bawadekar et al also quantified citrullinated proteins in lysates in a mouse model of TNF-α induced lung inflammation and showed that PADs other than PAD4 are responsible for inflammation-mediated protein citrullination in lungs (Bawadekar et al 2016). Moreover, Carmona-Rivera et al used Rh-PG to show that citrullinated proteins are abundantly generated during NET formation induced by either IgM or rheumatoid factor (Carmona-Rivera et al 2017).…”
Section: Activity-based Proteomic Probes Targeting the Padsmentioning
confidence: 99%